Psicologia da religião e espiritualidade contemporânea: contribuições da psicologia transpessoal - Oliveira, Fernanda Manzoli Marques de (2013)
This research was developed in the field of Psychology of Religion and sought to investigate the theoretical foundations of Humanistic Psychology and Transpersonal Psychology and their conceptions and considerations on the concept of spirituality. The humanistic school, a precursor of transpersonal psychology, presented a theory of spirituality fitted full of references to the transcendent, the urge to self-realization and self-actualization, to metaneeds and to peak experiences. However, it was up to the task of transpersonal psychology extend this framework further. This school studies altered states of consciousness and its applications, becoming the first psychological approach to expressly assume that humans have a spiritual dimension. Introduce new concepts like cosmic consciousness, ultimate values, mystical experience, sacredness of life, experience of Unity, responsiveness and maximum sensory awareness. Express a spirituality devoid of organized religion and an anthropological concept of searching for meaning, self-transcendence, supreme values and the search for unity with the cosmos